The impact of bottled Prolom water on lithogenesis of urinary tract - Bašić, prof. dr Dragoslav (Acta medicae Medianae, 2020)
Urolithiasis represents the most common urological condition nowadays, with rising trend of incidence and prevalence rates, according to geographical, climatic, ethnic, dietary and genetic factors. Prophylactic management of urolithiasis in terms of high fluid intake is of great importance in prevention of all types of urolithiasis. Prolom water has been categorized as a sodium hydro carbonic alkaline hypothermal oligomineral water. The aim of the study was to investigate the effects of bottled Prolom water intake on serum and urinary calcium and magnesium values, as well as on urinary pH and renal microlithiasis. A multicenter prospective trial included a total of 345 patients who had underwent Prolom water intake, in amount of 2,5 to 3 liters/daily, for 14 days, with follow up in three periods. Average values of calcium in serum (mmol/l) at day zero, 7th and 14th were: 2,24; 2,312 and 2,242, separately. Average values of calcium in urine (mmol/l) at day zero, 7th and 14th were: 1,046; 1,582 and 1,564, separately. Average values of magnesium in serum (mmol/l) at day zero, 7th and 14th were: 0,89; 0,82 and 0,81, separately. Average values of magnesium in urine (mmol/l) at day zero, 7th and 14th were: 1,09; 1,51 and 1,61, separately. Mean urinary pH values were: 6,3 at day zero; 5,9 at day 7th; and 6,8 at day 14th. Daily intake of 2,5-3 liters of bottled Prolom water has a favorable and antilithogenic effect on calcium oxalate and calcium phosphate urolithiasis.